Imaginarios globales y cartografías cosmopolitas: la modernidad literaria latinoamericana - Cabrera, Mario Federico David (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2018)
The book of the literary critic Mariano Siskind, Deseos cosmopolitas. Modernidad global y literatura mundial en América Latina, is inscribed in the debate for the functioning of the categories of cosmopolitanism and nationalism in the Latin American literature. The author argues that the "world" is presented as a desire for the Latin American writer as an epistemological exercise of exploration of otherness. To unfold this hypothesis, the book focuses on the analysis of two paradigmatic periods in the conformation of a cosmopolitan discourse in the literature of the continent: Modernism and Magical Realism. One of the central objectives of the book is to situate the analysis of global imaginaries and cosmopolitan cartographies of Latin American writers in the current debates about World Literature. To support this decision, the author elaborates a critique of the pedagogical practices linked to World Literature studies (with special reference to the North American university system) because they assume a universal and essentialist perspective. Finally, it is highlighted that the book denounces the scarce participation of Latin America (as a corpus, as a field of study and as a locus of enunciation) in debates about World Literature and imposes a work to think about the marginal specificity of the Latin American literature and the redefinition of global relations between institutions and imaginaries.